2008
DOI: 10.1074/jbc.m710290200
|View full text |Cite
|
Sign up to set email alerts
|

Single-stranded DNA-binding Protein Recruits DNA Polymerase V to Primer Termini on RecA-coated DNA

Abstract: Translesion DNA synthesis (TLS) by DNA polymerase V (polV) in Escherichia coli involves accessory proteins, including RecA and single-stranded DNA-binding protein (SSB). To elucidate the role of SSB in TLS we used an in vitro exonuclease protection assay and found that SSB increases the accessibility of 3 primer termini located at abasic sites in RecA-coated gapped DNA. The mutant SSB-113 protein, which is defective in protein-protein interactions, but not in DNA binding, was as effective as wild-type SSB in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…6A), although BRCA1 is necessary for their recruitment to DSBs. Third, in E. coli , the single-strand binding protein, SSB, recruits DNA polymerase V (Polη homolog) to the primer end of RecA-coated DNA for DNA synthesis (Arad et al, 2008). Unlike what was observed in bacteria, human RPA protein did not activate Polη (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…6A), although BRCA1 is necessary for their recruitment to DSBs. Third, in E. coli , the single-strand binding protein, SSB, recruits DNA polymerase V (Polη homolog) to the primer end of RecA-coated DNA for DNA synthesis (Arad et al, 2008). Unlike what was observed in bacteria, human RPA protein did not activate Polη (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, SSB may stimulate pol V Mut by simply decreasing the secondary structure of the long single-stranded template strand being copied. However, since SSB has been shown to physically interact with UmuC [9], the stimulation more likely occurs via a direct protein-protein interaction with pol V Mut that helps target the polymerase to the nascent primer terminus.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies revealed that rather than being an accessory factor to pol III, the UmuD2C complex possesses intrinsic polymerase activity, and was duly termed E. coli pol V [7,8]. Pol V has intrinsically weak DNA polymerase activity, but its catalytic activity can be stimulated in vitro in the presence the β-processivity clamp, RecA protein bound to ssDNA, and single-stranded-binding (SSB) protein [9-12]. …”
Section: Introductionmentioning
confidence: 99%
“…A second replication protein, the single-stranded DNAbinding protein (SSB), also interacts with many other proteins by way of a conserved peptide motif (229). In addition to interacting with the DnaG primase and the subunit of Pol III HE during DNA replication, SSB also binds to a range of DNA repair enzymes (9,30,86,100,135,148,162,225,229,243,263,275). These interactions are mediated by the final six to nine residues at the SSB C terminus, which in E. coli has the sequence MDFDDDIPF (229,275).…”
Section: Highly Conserved Protein Interaction Modules Within the ␤ Slmentioning
confidence: 99%